Gait speed is associated with death or readmission among patients surviving acute hypercapnic respiratory failure - Gatete Karege; Dina Zekry; Gilles Allali; Dan Adler; Christophe Marti (BMJ Open Respiratory Research)
Objectives Death or hospital readmission are frequent among patients surviving acute hypercapnic respiratory failure (AHRF). Severity scores are not valid to predict death or readmission after AHRF. Gait speed, a simple functional parameter, has been associated with hospital admission and death in the general population. The purpose of this study is to highlight an association between gait speed at hospital discharge and death or readmission among AHRF survivors.Design Secondary analysis of a prospective cohort study.Settings Single Swiss tertiary hospital, pulmonary division.Participants Patients were prospectively recruited to form a cohort of patients surviving AHRF in the intensive care unit between January 2012 and May 2015.Outcome measure Gait speed was derived from a 6 min walking test (6MWT) before hospital discharge. All predictive variables were prospectively collected. Death or hospital readmission were recorded for 6 months. Univariate and multivariate analyses were performed to evaluate the association between predictive variables and death or hospital readmission.Results 71 patients performed a 6MWT. 34/71 (48%) patients died or were readmitted to the hospital during the observation period. Median gait speed was 0.7 (IQR 0.3–1.0) m/s. At 6 months, 66% (25/38) of slow walkers (gait speed <0.7 m/s) and 27% (9/33) of non-slow walkers died or were readmitted to the hospital (p=0.002). In univariate analysis, gait speed was associated with death or readmission (HR 0.41; 95% CI 0.19 to 0.90, p=0.025). In a multivariate model adjusted for age, gender, body mass index, forced expired volume, heart failure and home mechanical ventilation, gait speed remained the only variable associated with death or readmission (multivariate HR: 0.35; 95% CI 0.14 to 0.88, p=0.025).Conclusion This study suggests that a simple functional parameter such as gait speed is associated with death or hospital readmission in patients surviving AHRF.Trial registration number NCT02111876.